The Beauty Trap: How the Pressure to Conform to Society’s and Media’s Standards of Beauty Leave Women Experiencing Body Dissatisfaction - Foo, Samantha Yee Yee (Auckland University of Technology, 2010)
From bound feet to fad diets, female bodies have been scrutinised and some endure beauty practices in order to fulfil the beauty ideal which is portrayed through art and media. When beauty is perceived as symbols of perfection and self-control, some women attempt to fulfil the beauty trap’s standards by transforming their bodies at the expense of their time, money and health. Questions have arisen in relation to the beauty trap and its relation to women’s body image. How do we define ideal feminine beauty? Is it defined as the ability to achieve the fashionable look where the female body can be changed easily through diets and makeovers? Or is it described as the ‘ultimate’ woman we see in fashion magazines or televised red carpet premieres? However, there are arguments that beauty is defined as the ability to embody femininity, self-esteem and personality altogether. As the famous adage goes “beauty is in the eye of the beholder”, some argue there is no right answer to describe female beauty. The thesis aims to gain insights into the beauty trap and help us understand the true definition of feminine beauty.
Keywords: Feminine beauty; Body dissatisfaction; Beauty practices; Women; Body image in women; Femininity